Answer:Simplifying
5(x + 2) = 3(x + 8)
Reorder the terms:
5(2 + x) = 3(x + 8)
(2 * 5 + x * 5) = 3(x + 8)
(10 + 5x) = 3(x + 8)
Reorder the terms:
10 + 5x = 3(8 + x)
10 + 5x = (8 * 3 + x * 3)
10 + 5x = (24 + 3x)
Solving
10 + 5x = 24 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
10 + 5x + -3x = 24 + 3x + -3x
Combine like terms: 5x + -3x = 2x
10 + 2x = 24 + 3x + -3x
Combine like terms: 3x + -3x = 0
10 + 2x = 24 + 0
10 + 2x = 24
Add '-10' to each side of the equation.
10 + -10 + 2x = 24 + -10
Combine like terms: 10 + -10 = 0
0 + 2x = 24 + -10
2x = 24 + -10
Combine like terms: 24 + -10 = 14
2x = 14
Divide each side by '2'.
x = 7
Simplifying
x = 7
Explanation: